Survival of Neonectria fuckeliana in woody material - Hopkins, A.J.M.; Dick, M.A.; Simpson, I.G. (New Zealand Plant Protection, 2008)
In southern New Zealand Neonectria fuckeliana is associated with a stem flute canker of Pinus radiata which can result in severe stem malformation and growth loss This research consisting of three distinct experiments aimed to determine pathogen survival in processed and unprocessed wood and woody debris In the first experiment the survival of the pathogen in living trees was examined by sampling trees infected with N fuckeliana in 6 different years In the second experiment the survival of the pathogen in woody debris was examined using 36 infected logs in a range of sizeclasses The logs were left on the forest floor in shaded and unshaded conditions and sampled for N fuckeliana after 4 and 9 months The third experiment examined the survival of the pathogen in processed wood Boards cut from infected trees were tested in six standard timber drying treatments Boards were sampled before and after drying to determine the presence of living N fuckeliana Neonectria fuckeliana was successfully isolated from trees at all infection times tested The fungus was also successfully isolated from 81 of logs after 9 months on the forest floor There was no significant difference between shaded and unshaded treatments Neonectria fuckeliana was not found in any boards following kilndrying but was successfully isolated from 69 of infected boards subjected to the two standard airdrying treatments for 9 weeks